2018
DOI: 10.1007/s00134-018-5269-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing predictive accuracy for outcomes of ventilator-associated events in an international cohort: the EUVAE study

Abstract: Respiratory infections (mainly VAT) were the most common complication. VAE algorithms only identified events with surrogates of severe oxygenation deterioration. As a consequence, IVAC definitions missed one fourth of the episodes of VAP and three fourths of the episodes of VAT. Identifying VAT (often missed by IVAC-plus criteria) is important, as VAP and VAT have different impacts on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 37 publications
4
61
0
2
Order By: Relevance
“…Previous studies reported similar findings regarding the correlation between VAE and VAP [6,11,12]. However, few studies prospectively evaluated the incidence of VAT in patients with VAE [11,13]. Among the 262 diagnosed episodes of VAE, only 6 (2%) were possibly related to VAT.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies reported similar findings regarding the correlation between VAE and VAP [6,11,12]. However, few studies prospectively evaluated the incidence of VAT in patients with VAE [11,13]. Among the 262 diagnosed episodes of VAE, only 6 (2%) were possibly related to VAT.…”
Section: Discussionmentioning
confidence: 61%
“…Direct comparisons of the performance characteristics of the CDC/NHSN, CPIS, HELICS, and Johanson criteria have not previously been reported. Moreover, only two studies were identi ed that compared VAP diagnostic algorithms [32,66]. HELICS was chosen as the reference standard due as it has been reported to have the best performance characteristics, is widely used internationally, and has been used as the reference standard for numerous other studies [2,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…However, the criteria used to diagnose VAP vary widely, which impacts reports of incidence and outcomes. Moreover, the standard diagnosis comparator to which algorithms are compared as well as and inter-algorithm agreement varies signi cantly (Table 2), making inter-study comparisons di cult [32]. Even with strict criteria, the interpretation of some factors, such as the radiographs or the aspect of tracheal secretions, can be very subjective.…”
Section: Introductionmentioning
confidence: 99%
“…by inducing acute respiratory distress syndrome, hydric overload). Otherwise, it could be IVAC due to a ventilator-associated respiratory infection that not meet PVAP criteria and even though VAP or VAT episodes that not meet any VAE criteria as it has been reported (Fan et al, 2016;Ramírez-Estrada et al, 2018;Peña-López et al, 2017;Sim et al, 2016). Thus, infectious ventilator-associated complications and non-infectious associated complications could be correlated with IVAC-plus and VAC events, respectively, IVAC-plus encompassing IVAC and PVAP with the purpose of avoiding missing some ventilator-associated infections but not referring exclusively to them.…”
Section: Vae Surveillance Updates and Clinical Correlationmentioning
confidence: 99%